DISASTER RISK MANAGEMENT AS A PROMOTER OF SMART EDUCATIONAL SYSTEMS - Vargas Hernández, Annie (2022)
The objetive of this research is to visualize disaster risk management as a prometer of intelligent educational systems. This is due to the fact that the manifestation of a disaster in the educational system can have multiple effects on its functionality and can even contribute to the increase of social gaps between the most vulnerable groups, as well as compromising the quality and continuity of the educational processes. The educational system must fulfill its emancipatory mission; therefore, it is necessary for this to be a sustainable and resilient system and this may be possible if the educational system is transformed into an intelligent organization that allows systemic work between this and DRM.